Kebijakan Inovatif Kepala Sekolah Efektif dalam Pengembangan Mutu SDM di MIN 1 Yogyakarta - Alfian Ghofar Rahmat, Farah; Mifroh, Nazilatul; Annur, Aan Fadia (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
A student's success in studying mathematics is marked by achievement. In composition, drawing conclusions is an important part of planning activities. This research aims to explain and test in detail the principal's leadership in drawing conclusions made by the principal of MIN 1 Yogyakarta in developing the quality of human resources and explaining the implementation of initiatives. This research is a qualitative descriptive research with a background in MIN 1 Yogyakarta. Data collection methods use observation, interviews and data collection. The results of this research show that the principal of MIN 1 Yogyakarta is very agile and disciplined in advancing the school so that it is superior and more students achieve, looking in as much detail as possible for problems that may be obstructing them and being thorough so that bad things do not interfere with the progress of the school, encouraging the teachers must be diligent and disciplined with their time so that they can be invited to progress.